DETERMINAN TINGKAT PENERAPAN STANDAR NASIONAL PENDIDIKAN DI BERBAGAI JENJANG SEKOLAH - Rambat Nur Sasongko (Manajer Pendididikan, 2019)
Abstract: “Determinants of the Level of Application of National Standards of Education in Various Schools”. National Education Standards (NES) are guidelines for managing education in schools. High quality schools, apply NES well. However, it is suspected that many schools lack serious implementation of SNP. Therefore, the achievement of the application of NES is not good. In other words it has a less standard status. This study aims to describe the determinants of the level of NES implementation at various levels of school. The research method uses descriptive studies. The research subjects were principals, teachers, administrative staff, school committees, and support staff in elementary, junior high, high school and vocational schools in the Lubuklinggau region, Musi Rawas, and North Musi Rawas. Data collection techniques are collected by interviews, observation, and documentation studies. Techniques for analyzing data with “descriptive statistics” and "flow analysis" on an ongoing basis. The results of the study show that the application of SNP at various levels of the school has different achievements from one school to another. It really depends on the resources and potential of the school that is owned. In general, almost all schools have not been able to apply the NES effectively. This is determined by two main factors, namely internal factors and external factors. Internal factors such as concern for school residents, availability of resources, and availability of budgets. External factors such as the support of school committees, parents, communities, government, and donors.Key words: National Education Standards, determinants, various schools